Analysis of the Competitiveness of Indonesia Tourism Price Compared to the Competitors (Demand Elasticity Approach) - Utami, Rayinda Citra; Hartono, Djoni Hartono; Awirya, Agni Alam (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2016)
This study applies Almost Ideal Demand System models to examine Indonesiaâs competitiveness as a tourist destination compared to two main competitor countries. The model was used to estimate the sensitivity of tourism demand from seven tourist-main market countries to price changes, the touristsâ total budget and global economic crisis. The model estimated result meets the assumptions of the demand theory: homogeneity and symmetry. The elasticity price shows that Indonesia is more competitive than Thailand among Australian and American tourists; while Indonesia is more competitive than Malaysia among American tourists. The research result also shows that the tourism price is the main determinant affecting the allocation of tourist expenditure in the three destinations.